2018
DOI: 10.5194/hess-22-1017-2018
|View full text |Cite
|
Sign up to set email alerts
|

Climate change alters low flows in Europe under global warming of 1.5, 2, and 3 °C

Abstract: Abstract. There is growing evidence that climate change will alter water availability in Europe. Here, we investigate how hydrological low flows are affected under different levels of future global warming (i.e. 1.5, 2, and 3 K with respect to the pre-industrial period) in rivers with a contributing area of more than 1000 km 2 . The analysis is based on a multi-model ensemble of 45 hydrological simulations based on three representative concentration pathways (RCP2.6, RCP6.0, RCP8.5), five Coupled Model Interco… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
145
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 179 publications
(154 citation statements)
references
References 50 publications
9
145
0
Order By: Relevance
“…This is fundamentally different from observational records (which are subject to changing management conditions and transient climate) and transient model simulations. Finally, by combining multiple GCMs with multiple GHMs, the dominant sources of uncertainty in projections (meteorological variability, hydrological response, or model formulation) can be isolated (e.g., Marx et al, 2018;Thober et al, 2017). The design of the large ensembles used here, in combination with the empirical distribution approach, limits the need for (statistical) assumptions, descriptions, and corrections.…”
Section: Discussionmentioning
confidence: 99%
“…This is fundamentally different from observational records (which are subject to changing management conditions and transient climate) and transient model simulations. Finally, by combining multiple GCMs with multiple GHMs, the dominant sources of uncertainty in projections (meteorological variability, hydrological response, or model formulation) can be isolated (e.g., Marx et al, 2018;Thober et al, 2017). The design of the large ensembles used here, in combination with the empirical distribution approach, limits the need for (statistical) assumptions, descriptions, and corrections.…”
Section: Discussionmentioning
confidence: 99%
“…Both DynWat and PCR-GLOBWB 2 use ERA-40 and ERA-Interim forcing Dee et al, 2011;Uppala et al, 2005), with an elevation correction to account for spatial heterogeneity in the elevation (Sutanudjaja et al, 2018), to generate water temperature and runoff estimates for the period 1960-2014. The hydrological input from PCR-GLOBWB 2 has been extensively validated in multiple studies and shown to produce accurate estimates of daily discharge (Sutanudjaja et al, 2018;Van Beek et al, 2011), simulate hydrological extreme events (e.g., He et al, 2017;Marx et al, 2018;Thober et al, 2017;Wada et al, 2013;Wanders & Van Lanen, 2015), and reproduce decadal teleconnections (e.g., Wanders & Wada, 2015b). The river routing in DynWat is similar to that of PCR-GLOBWB and for the discharge simulation performance, we refer to Sutanudjaja et al (2018) for the latest evaluation.…”
Section: Comparing Model Resolutionsmentioning
confidence: 99%
“…In order to systematically attribute the hydrological changes over the Sanjiangyuan region, both hydrological variables/parameters (e.g., ground temperature, soil frozen duration, streamflow, TWS) and the hydrological extremes (i.e., low flows and high flows) were investigated in this study. Low flows and high flows were defined as 5 and 95% percentile for daily streamflow time series in a specific year, where this volume-based definition was widely used in trend analysis (Burn, 2008;Hodgkins & Dudley, 2016;Marx et al, 2018). As introduced in Marx et al (2018), low flows could cause shortage of surface or subsurface water resources, which has the potential to impact hydrological drought.…”
Section: The Attribution Methodsmentioning
confidence: 99%
“…Low flows and high flows were defined as 5 and 95% percentile for daily streamflow time series in a specific year, where this volume-based definition was widely used in trend analysis (Burn, 2008;Hodgkins & Dudley, 2016;Marx et al, 2018). As introduced in Marx et al (2018), low flows could cause shortage of surface or subsurface water resources, which has the potential to impact hydrological drought. High flows are indicators for flooding (Lee et al, 2015), and are usually related to heavy rainfall (Groisman et al, 2001).…”
Section: The Attribution Methodsmentioning
confidence: 99%